If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x-36=2(x+11)
We move all terms to the left:
4x-36-(2(x+11))=0
We calculate terms in parentheses: -(2(x+11)), so:We get rid of parentheses
2(x+11)
We multiply parentheses
2x+22
Back to the equation:
-(2x+22)
4x-2x-22-36=0
We add all the numbers together, and all the variables
2x-58=0
We move all terms containing x to the left, all other terms to the right
2x=58
x=58/2
x=29
| 8x+4(4x-3)=4(5x+4)-4 | | 11x-1=-15 | | 4x2+24x+35=0 | | 4x-36=2(x=11) | | (g+4)-3g=+g | | X2-5x-14=-8x-4 | | 100+0.40x=60+0.50x | | 20+10x=15+7x | | -5n-8(1=7n)=-08 | | X2-10x+18=9 | | 8x-6=7(x+6)-4 | | X2+13x+14=3x-2 | | 4(x+2)=5-2(x-3) | | 41m-10m^2+45=0 | | X2-3x-6=4 | | 1.5=2x+5x+3x | | 6/5=100/x | | 21=x+2x+12 | | 3x-12=-3x-36 | | m+2/5=2m-11/7 | | 0.3=2.4+y | | 5(n+2)=3/4(5+10n) | | 5x-2=13x+11 | | x2-7x-17=1 | | n+(n+4)=-56 | | 3(z+1)=4z-11 | | -6(x-4)+1=3(x-5) | | n+(n+2)=-56 | | 12=3(m+6) | | 5-2x=-4x-19 | | -4x+4=3x-11 | | 5x²-10x=0 |